2020
DOI: 10.2807/1560-7917.es.2020.25.2.1900749
|View full text |Cite
|
Sign up to set email alerts
|

Co-circulation of multiple enterovirus D68 subclades, including a novel B3 cluster, across Europe in a season of expected low prevalence, 2019/20

Abstract: Enterovirus D68 (EV-D68) was detected in 93 patients from five European countries between 1 January 2019 and 15 January 2020, a season with expected low circulation. Patients were primarily children (n = 67, median age: 4 years), 59 patients required hospitalisation and five had severe neurologic manifestations. Phylogenetic analysis revealed two clusters in the B3 subclade and subclade A2/D. This circulation of EV-D68 associated with neurological manifestations stresses the importance of surveillance and diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 19 publications
(16 reference statements)
9
44
0
Order By: Relevance
“…This study underpins the strength of the ENPEN consortium, which brings together virologists, public health experts, infectious disease doctors, and scientists across Europe to enable rapid detection and early warning through standardized surveillance. Previous studies using Nextstrain with 2 EV-D68 datasets have shown the value of combining demographic and phylogenetic analysis, both as retrospective (33) and real-time analysis (34). The E30 dataset and the 2 EV-D68 datasets (33,34) available on Nextstrain represent large nonpolio enterovirus datasets that support real- Differences in surveillance systems, case definitions, and sample selection between institutes and countries make standardized data collection difficult, particularly for denominator data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study underpins the strength of the ENPEN consortium, which brings together virologists, public health experts, infectious disease doctors, and scientists across Europe to enable rapid detection and early warning through standardized surveillance. Previous studies using Nextstrain with 2 EV-D68 datasets have shown the value of combining demographic and phylogenetic analysis, both as retrospective (33) and real-time analysis (34). The E30 dataset and the 2 EV-D68 datasets (33,34) available on Nextstrain represent large nonpolio enterovirus datasets that support real- Differences in surveillance systems, case definitions, and sample selection between institutes and countries make standardized data collection difficult, particularly for denominator data.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using Nextstrain with 2 EV-D68 datasets have shown the value of combining demographic and phylogenetic analysis, both as retrospective (33) and real-time analysis (34). The E30 dataset and the 2 EV-D68 datasets (33,34) available on Nextstrain represent large nonpolio enterovirus datasets that support real- Differences in surveillance systems, case definitions, and sample selection between institutes and countries make standardized data collection difficult, particularly for denominator data. The differences in data collection proved to be a limitation in our study, and the extent of the circulation of the different strains remains unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, many of the previously identified sites of sequence similarity to neurotropic enteroviruses in subclade B1 were not present ( 69 ). Nonetheless, the B3 subclade was dominant in the 2016 and 2018 outbreaks in the United States and Europe, including among patients with AFM ( 70 , 71 , 72 , 73 ), and in 2018, all US isolates were from clade B3 ( 74 ).…”
Section: Molecular Evolution Of Contemporary Strainsmentioning
confidence: 99%
“…Number of beds available for COVID-19 treatment is likely much lower. 4 Number of available beds in Intensive Care Units (ICUs). The default values are rough estimates indicating total capacity.…”
Section: Parameter Estimationmentioning
confidence: 99%